Dementia: beyond disorders of mood - Petty, Stephanie; Dening, Tom; Coleston-Shields, Donna Maria; Griffiths, Amanda (Taylor & Francis, 2018)
This editorial will present the growing argument in the research literature that mood disorders, as defined by psychiatric diagnostic criteria, do not well serve individuals with dementia. This is important because anxiety and depression are our most used and most influential ways of understanding a highly prevalent and personally important experience in dementia: emotion. As such, there is a need to review how the disorders are currently conceptualised since they may have limited applicability for individuals with dementia, and consider what alternatives there might be. Agitation is offered as a lesson in how imprecise descriptions of behaviour can exclude the internal world of people with dementia. In our research to explore how the emotional experiences of individuals with dementia are understood, we consider what might lie beyond disorders of mood.